2003
DOI: 10.1038/sj.ijo.0802393
|View full text |Cite
|
Sign up to set email alerts
|

Fat oxidation, body composition and insulin sensitivity in diabetic and normoglycaemic obese adults 5 years after weight loss

Abstract: OBJECTIVE:To investigate whether normal glucose-tolerant and type II diabetic overweight adults differ in response to weight regain with regard to substrate oxidation and metabolic parameters. METHODS: A total of 15 overweight-obese subjects: seven normal glucose tolerant (NGT) and eight with type II diabetes (DM) were restudied 5 y after significant weight loss. Prediet, after 28 days calorie restriction and at 5 y, subjects were characterised for weight, height, waist-to-hip ratio (WHR) and body composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Several small case-control studies among middle-aged persons found either no differences in fat distribution [18][19][20] or an unfavorable fat distribution with more truncal fat and less peripheral fat in persons with type 2 diabetes compared with healthy controls. 21,22 Fat distribution in older adults with type 2 diabetes was examined in a small casecontrol study.…”
Section: Diabetes and Fat Distributionmentioning
confidence: 99%
“…Several small case-control studies among middle-aged persons found either no differences in fat distribution [18][19][20] or an unfavorable fat distribution with more truncal fat and less peripheral fat in persons with type 2 diabetes compared with healthy controls. 21,22 Fat distribution in older adults with type 2 diabetes was examined in a small casecontrol study.…”
Section: Diabetes and Fat Distributionmentioning
confidence: 99%
“…Maiolo et al 6 , in a study of body composition and pulmonary function in matched type 2 diabetes and control groups of women reported more lean mass and nonsignificantly less fat mass in type 2 diabetes. Poynten et al 7 observed no difference in percentage TBF between weight and body mass index (BMI)-matched controls and subjects with type 2 diabetes. Studies that report fat as a proportion of total body weight often find subjects with type 2 diabetes to have higher percentage of fat.…”
Section: -4mentioning
confidence: 99%
“…[5][6][7] Studies that report fat as a proportion of total weight often find subjects with type 2 diabetes to have a higher proportion of body weight as fat. 8 In contrast, we found that after adjustment by regression for weight, height, race/ethnicity, sex and age, subjects with type 2 diabetes had less total fat mass and more lean mass than controls.…”
Section: Altered Body Composition In Type 2 Diabetes S Heshka Et Almentioning
confidence: 99%
“…It is also obvious that the criteria for correction of therapeutic rations in diabetics with type 2 disease and cardiovascular patients should be based on analysis of patients' metabolograms, body composition characteristics, and data of standard biochemical and hormone tests [2,4,8]. Final correction of therapeutic rations should be based on metabolograms at rest and metabolograms recorded under other physiological conditions, including exercise and test meals.…”
Section: Resultsmentioning
confidence: 99%
“…This principle is based on the fact that amino acid oxidation rate determines the protein requirements of the organism [5,6,10,11]. This assumption can be fully extrapolated to glucose and fatty acid oxidation rates.Study of oxidative metabolism by endogenous rates of glucose, amino acid, and fatty acid oxidation by indirect calorimetry at rest and during exercise provides a tentative evaluation of metabolic disorders in maladaptation and development of nutrition-dependent disease [7][8][9]. However, the oxidation rates of the main macronutrients should be converted to the units of body weight and its constituents, primarily fatty and lean weights, which fact is virtually neglected at present.…”
mentioning
confidence: 98%